2021
DOI: 10.1155/2021/6613786
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Short-Term Tacrolimus Exposure on Rat Liver: An Insight into Serum Antioxidant Status, Liver Lipid Peroxidation, and Inflammation

Abstract: Tacrolimus (TAC) is an immunosuppressive drug, optimally used for liver, kidney, and heart transplant to avoid immune rejection. In retrospect, a multitude of studies have reported effects of TAC, such as nephrotoxicity, diabetes, and other complications. However, limited information is available regarding short-term exposure of TAC on the liver. Therefore, the present study was designed to unravel the effects of short-term exposure of TAC on a rat model. The animal model was established by TAC administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
1
5
1
Order By: Relevance
“…While liver and kidney of the aSCT + TAC@TGM group exhibited normal histological appearance. These results were consistent with earlier studies, which reported that obvious toxic effects of high-dose (aSCT + TAC-TP group) or long-term systemic use (aSCT + TAC-IP group) of TAC on liver and kidney [ 18 , 50 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…While liver and kidney of the aSCT + TAC@TGM group exhibited normal histological appearance. These results were consistent with earlier studies, which reported that obvious toxic effects of high-dose (aSCT + TAC-TP group) or long-term systemic use (aSCT + TAC-IP group) of TAC on liver and kidney [ 18 , 50 ].…”
Section: Resultssupporting
confidence: 93%
“…(Sakura Finetek Inc.) and then frozen sectioned (10 μm) using a Leica CM1950 cryostat (Leica Camera Inc.). Hematoxylin–eosin (HE) staining was applied for general morphology observation according to the previous method [ 18 ]. Image-J software (Wayne Rasband, National Institutes of Health) was used to calculate the percentage of area occupied by inflammatory cells in the visual field.…”
Section: Methodsmentioning
confidence: 99%
“…Its greater immunosuppressive effects and lower incidence of adverse reactions (compared with ciclosporin) have established itself as one of the common immunosuppressive protocols in organ transplantation (Kelly et al., 2004; Rawal & Yazigi, 2017). Currently, the most commonly used immunosuppressive agent is Tac in liver transplant patients, but the similar dosages of effectiveness and toxicity cause adverse effects, which limits its clinical application in liver transplantation (Fatima et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the most commonly used immunosuppressive agent is Tac in liver transplant patients, but the similar dosages of effectiveness and toxicity cause adverse effects, which limits its clinical application in liver transplantation (Fatima et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The primer pairs used were Shh (forward: CAATTACAACCCCGACATCA, reverse: AGTCACTCGAAGCTTCACTCC), Ihh (forward: TCAGCGATGTGCTCATTTTC, reverse: CCTCGTGAGAGGAGCATAGG), Ptch (forward: ATTTCTTGCCCTTGGTGTTG, reverse: GAAGGCAGTGACATTGCTGA), Smo (forward: AGAAGGCCTTGGCAATCA, reverse: GAAGCCCATTCCTGATTGTG), Hhip (forward: TGTGCCGTGGATCGAC, reverse: GATCTCCGAACACGTAGCTT), Gli‐3 (forward: CCCTCTCTCCCTTATCGTG, reverse: AAGGCAAGTCTGGATACGTT), TNF‐α (forward: ACA AGG CTG CCC CGA CTA T, reverse: CTC CTG GTA TGA AGT GGC AAA TC), NFκβ (forward: CAT GGC AGA CGA CGA TCC TT, reverse: AAG GTA TGG GCC ATC TGT TGA), Socs3 (forward: AGCTCCAAAAGCGAGTACCA, reverse: TGACGCTCAACGTGAAGAAG), and GAPDH (forward: AGAGACAGCCGCATCTTCTT, reverse: TGCATTGCTGACAATCTTGA). Expressions were analyzed using RT‐PCR 25,26 …”
Section: Methodsmentioning
confidence: 99%